Digital Transformation in Public Administration: Challanges and Opportunities in the Age of AI and Big Data - Hardianto, Toto; Mustafa, Mustafa; Suleman, Yakub; Aiman Mubarak, Muh Nurul; Triadi, Feby (Universitas Negeri Makassar, 2025)
The rapid evolution of digital technologies is reshaping the landscape of public administration worldwide. This paper examines the integration of Artificial Intelligence (AI) and Big Data into public sector processes, analyzing their potential to enhance operational efficiency, transparency, and citizen engagement. Through a mixed-methods approach, combining literature review, surveys, and interviews with government officials and technology experts. Key issues include data security, digital inequality, and algorithmic bias. The paper concludes by recommending policy frameworks, capacity-building initiatives, and ethical guidelines that can help public administrations harness the potential of AI and Big Data while mitigating associated risks. The result of the study reveals that AI can improve decision-making, automate tasks, and optimize resource allocation, while Big Data enables better policy-making and public service delivery. However, challenges such as data security, digital inequality, and algorithmic bias must be addressed. The paper concludes with recommendations for ethical guidelines, policy frameworks, and capacity-building initiatives to harness the benefits of AI and Big Data while mitigating associated risks.